2007
DOI: 10.7150/ijbs.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Anion Radical Scavenging Activities of Herbs and Pastures in Northern Japan Determined Using Electron Spin Resonance Spectrometry

Abstract: Free radicals are not only destructive to the living cells but also reduce the quality of animal products through oxidation. As a result the superoxide anion radical (O2・-), one of the most destructive reactive oxygen species, is a matter of concern for the animal scientists as well as feed manufacturers to ensure the quality of product to reach consumers demand. The superoxide anion radical scavenging activities (SOSA) of water and MeOH extracts of 2 herbs and 9 pasture samples collected from lowland and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 15 publications
(14 reference statements)
0
30
0
Order By: Relevance
“…It was found that antioxidants ameliorated heat stress in sheep (Chauhan et al, 2014). Therefore, due to the antioxidant (Al-Mamun et al, 2007a) and also the higher plasma α-tocopherol content of PL-diet, the rectal temperature was comparatively lower during the HE when animals were offered the PL-diet compared with the MH-diet. Environments did not affect heart rate, which was in accordance with the previous findings by Sano et al (1983) in sheep.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It was found that antioxidants ameliorated heat stress in sheep (Chauhan et al, 2014). Therefore, due to the antioxidant (Al-Mamun et al, 2007a) and also the higher plasma α-tocopherol content of PL-diet, the rectal temperature was comparatively lower during the HE when animals were offered the PL-diet compared with the MH-diet. Environments did not affect heart rate, which was in accordance with the previous findings by Sano et al (1983) in sheep.…”
Section: Discussionmentioning
confidence: 98%
“…Higher α-tocopherol is an indication of higher free radical scavenging activities (FRSA). It was reported that plantain was superior to other traditional pastures and herbs in Japan to FRSA (Al-Mamun et al, 2007a). α-Tocopherol is the most frequently used lipid-soluble free radical scavenger, and it may scavenge the free radical on the surface of cell membrane efficiently and finally terminate the lipid oxidation (Buckley et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide anion radical is one of the strongest ROS among the free radicals and get converted to other harmful reactive oxygen species such as hydrogen peroxide and hydroxyl radical causing damages to biomolecules. They induce oxidative damage in lipids, protein and DNA by producing powerful and dangerous hydroxyl radicals, hydrogen peroxide, peroxy nitrite and singlet oxygen ultimately (Al-Mamun et al, 2007). Here superoxide radicals are generated in PMS-NADH systems by oxidation of NADH and assayed by the reduction of nitro-bluetetrazolium (NBT), measured at 560 nm.…”
Section: In Vitro Free Radical Scavenging Activity:-mentioning
confidence: 99%
“…Superoxide anion radical-scavenging activity (SOSA) was investigated following the method in previous reports [12][13][14][15]. O 2 ˑw as generated from the HPX-XOD reaction.…”
Section: Esr Spin-trapping Analysesmentioning
confidence: 99%